“Where there's smoke, there's fire": The impact of recent burnings in Brazil and their effects on air quality for outdoor physical exercise (Research, Society and Development, 2025)
Brazil’s alarming surge in wildfires in 2024 has led to a severe deterioration in air quality, particularly affecting the Amazon, Cerrado, and Pantanal biomes. The smoke, rich in fine particulate matter (PM2.5), poses significant health threats, including respiratory and cardiovascular diseases, and has raised growing concerns about the safety of outdoor physical activity. Prolonged exposure to these pollutants can trigger systemic oxidative stress, airway irritation, and inflammation, further compromising health outcomes for individuals who exercise outdoors. The objective of this article is to outline strategies to mitigate these adverse effects and offer practical recommendations for exercising safely when ambient air quality is compromised. This article examines the complex balance between the proven benefits of physical activity and the hazards of exercising in polluted environments, while providing practical, evidence-based recommendations to mitigate risks. Suggested strategies include prioritizing indoor training spaces equipped with HEPA or MERV-13 filtration, adjusting workout timing, intensity, and duration according to air quality index, offering specific guidance for vulnerable populations (such as children, older adults, and individuals with asthma or heart disease), and adopting protective measures like N95 masks, hydration, and skin protection. These insights aim to guide safe exercise practices during periods of compromised air quality.